2020
DOI: 10.1136/jmedgenet-2020-107059
|View full text |Cite
|
Sign up to set email alerts
|

Blood functional assay for rapid clinical interpretation of germline TP53 variants

Abstract: BackgroundThe interpretation of germline TP53 variants is critical to ensure appropriate medical management of patients with cancer and follow-up of variant carriers. This interpretation remains complex and is becoming a growing challenge considering the exponential increase in TP53 tests. We developed a functional assay directly performed on patients’ blood.MethodsPeripheral blood mononuclear cells were cultured, activated, exposed to doxorubicin and the p53-mediated transcriptional response was quantified us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…As such, individuals with these variants remain underinformed about their potential for cancer risk and ineligible for advanced cancer screening by MRI that is offered to Li Fraumeni carriers. Recently, some groups have attempted to address this issue, by establishing the functionality of p53 variants in nontransformed cell lines containing endogenous p53 variants following exposure to genotoxic stress ( 36 , 37 ). However, such studies have been low throughput, and they require a genotoxic stress.…”
Section: Discussionmentioning
confidence: 99%
“…As such, individuals with these variants remain underinformed about their potential for cancer risk and ineligible for advanced cancer screening by MRI that is offered to Li Fraumeni carriers. Recently, some groups have attempted to address this issue, by establishing the functionality of p53 variants in nontransformed cell lines containing endogenous p53 variants following exposure to genotoxic stress ( 36 , 37 ). However, such studies have been low throughput, and they require a genotoxic stress.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite large-scale characterization of pediatric cancer genomes, there are typically variants identified in cancer-related genes for which no known functional impact on cancer onset or progression can be discerned. This reality applies even to the most frequently mutated genes in cancer such as TP53, although exciting new approaches to contextualizing variants in this gene have been recently published [ 14 , 15 ].…”
Section: Overview Of Genomic Toolsmentioning
confidence: 99%
“…In terms of clinical approaches, diagnostic tests are under development that show the potential to provide personalized cancer risk assessments. Recent investigations demonstrated that TP53 variant carriers can be discriminated from wild-type p53 carriers by measuring functional and molecular characteristics such as p53 target gene expression patterns or DNA-binding capacity ( 71-73 ). Raad and coworkers ( 71 ) developed a blood-based assay where peripheral blood mononuclear cells are cultured, activated, treated with doxorubicin, and probed for the expression of p53 and its target genes.…”
Section: Improving Tp53 Variant Classificationsmentioning
confidence: 99%
“…Recent investigations demonstrated that TP53 variant carriers can be discriminated from wild-type p53 carriers by measuring functional and molecular characteristics such as p53 target gene expression patterns or DNA-binding capacity ( 71-73 ). Raad and coworkers ( 71 ) developed a blood-based assay where peripheral blood mononuclear cells are cultured, activated, treated with doxorubicin, and probed for the expression of p53 and its target genes. They discovered distinct functional profiles when comparing 8 P/LP variant carriers with 51 wild-type individuals, and, importantly, this strategy could be applied to VUS and low penetrance alleles.…”
Section: Improving Tp53 Variant Classificationsmentioning
confidence: 99%